ARABIC LANGUAGE IN GOVERNMENT AND PRIVATE SCHOOLS IN NIGERIA/ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙÙŠ Ø§Ù„Ù…Ø¯Ø§Ø±Ø³ Ø§Ù„ØÙƒÙˆÙ…ÙŠØ© ÙˆØ§Ù„Ø£Ù‡Ù„ÙŠØ© ÙÙŠ Ù†ÙŠØ¬ÙŠØ±ÙŠØ§ - Ibraheem, Lateef Onireti; Jamiâ€™u, Aliyu Muhammad (Ijaz Arabi Journal of Arabic Learning, 2019)
Private and Public schools have contributed immensely to the growth and development of Arabic Language in Nigeria. Even though the method of teaching in the private Arabic school before the advent of the colonialism in Nigeria was informal, Arabic developed to the extent of being used to produce literary works. In the first quarter of the twentieth century, formal private Arabic schools, as well as the public ones, were established in the country. From then, especially after the independent of Nigeria, the situation of Arabic schools is changing for the better. That notwithstanding, these schools are still encountering problems. The aim of this study, therefore, was to examine the current situations of Arabic language and its problem and prospects in Nigerian private and public schools vis a vis its growth and development. The study concluded that while the case of Arabic in Private Schools in Nigeria is perfect, it appears dismal in public schools. It is therefore recommended that the governments’ recognition and support for Arabic schools and programmes and adequate review of Arabic curricula Arabic will attain the greater height in Nigeria.